2023
DOI: 10.1017/wsc.2023.42
|View full text |Cite
|
Sign up to set email alerts
|

Herbicide resistance in Bromus spp.: a global review

Victor H. V. Ribeiro,
Judit Barroso,
Caio A. C. G. Brunharo
et al.

Abstract: This review summarizes what is currently known about herbicide resistance in Bromus spp. worldwide. Additional information on the biology and genetics of Bromus spp. is provided to further the understanding of resistance evolution and dispersal of the different species. Cases of herbicide resistance have been confirmed in Bromus catharticus Vahl., Bromus commutatus Schrad.; syn. Bromus racemosus L., Bromus diandrus Roth, Bromus japonicus Thunb.; syn. Bromus arvensis L., Bromus madritensis L., Bromus rigidus Ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 144 publications
0
3
0
Order By: Relevance
“…The emergence of herbicide resistance has caused a significant challenge to effective weed control, threatening crop production and food security. More importantly, the fast evolution of herbicide resistance in brome species suggests that herbicide resources available for brome control have been diminishing ( Ribeiro et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…The emergence of herbicide resistance has caused a significant challenge to effective weed control, threatening crop production and food security. More importantly, the fast evolution of herbicide resistance in brome species suggests that herbicide resources available for brome control have been diminishing ( Ribeiro et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of competitive native species is also used, which can also effectively limit the development of smooth brome through natural competition [28,29,33,34]. Herbicide treatments can be effective, especially when applied selectively, reducing negative impacts on non-target species [35][36][37][38][39]. Good results are achieved by mechanical removal and controlled burning, which can disrupt the growth cycle of bromegrass and reduce its seed bank in the soil [29,40].…”
Section: Introductionmentioning
confidence: 99%
“…from across Australia, Europe, and the USA. 9,10 The molecular mechanisms conferring resistance to ALS inhibitors in brome grass have been relatively well-studied and are similar to those in other weed species, namely: point mutations of the ALS enzyme which decrease its affinity for the herbicide [11][12][13] ; overexpression of the ALS gene, providing higher levels of enzyme to maintain flux through its metabolic pathway 14 ; and enhanced detoxification of the herbicide, decreasing the concentration of ALS inhibitor in the plant cell. 11,14,15 By contrast, mechanisms of resistance to ACCase inhibitors have been elucidated only in one study with Bromus tectorum L. 16 Extensive research in other resistant grass weeds, however, has revealed that metabolic detoxification of ACCase inhibitors, likely mediated by cytochrome P450 mono-oxygenase(s) (in concert with glutathione transferase in some cases), occurs in a number of species.…”
Section: Introductionmentioning
confidence: 99%